Narrating cultural encounter representation of India in select enlightenment women writers - Chatterjee, Arnab (Routledge, Taylor & Francis Group, 2022)
British women writers and India vis-à-vis the context of the Enlightenment -- "Enchanting quarter of the globe" : representation of India in Phebe Gibbes's Hartly House, Calcutta -- "A presumptuous effort" : representation of India in Translations of the letters of a Hindoo Rajah -- "My Indian venture" : representation of India in Lady Morgan's The Missionary: an Indian tale -- Mapping the gaze of the British women travellers : representation of India in Jemima Kindersley and Eliza Fay
Literaturverzeichnis: Seite 177-187
Keywords: Geschichte 1777-1815; Indien -- Motiv; Roman; Schriftstellerin; Reisebericht; Großbritannien; English prose literature / 18th century / History and criticism; English literature / Women authors / History and criticism; Travelers' writings, English / India / History and criticism; Colonies in literature; Enlightenment; Literary criticism; India / In literature